CONTROLS ON LOW-PRESSURE ANATEXIS - Gerbi C.C.; Johnson S.E.; Koons P.O. (My University, 2006)
Low-pressure anatexis, whereby rocks melt in place after passing through the andalusite stability field, develops under more restricted conditions than does low-pressure metamorphism. Our thermal modelling and review of published work indicate that the following mechanisms, operating alone, may induce anatexis in typical pelitic rocks without inducing wholesale melting in the lower crust: (i) magmatic advection by pervasive flow; (ii) crustal-scale detachment faulting; and (iii) the presence of a high heat-producing layer. Of these, only magmatic advection by pervasive flow and crustal-scale detachment faulting have been shown quantitatively to provide sufficient heat to cause widespread melting. Combinations of the above mechanisms with pluton-scale magmatic advection, shear heating, removal of the lithospheric mantle, or with each other provide additional means of developing suitable high temperatures at shallow crustal levels to generate low-pressure anatexis. © 2006 Blackwell Publishing Ltd.
Keywords: ANATEXIS; LOW-PRESSURE METAMORPHISM; THERMAL MODELLING